2021
DOI: 10.21873/invivo.12293
|View full text |Cite
|
Sign up to set email alerts
|

Curative Radiotherapy in Elderly Patients With Muscle Invasive Bladder Cancer: The Prognostic Role of Sarcopenia

Abstract: Background/Aim: To evaluate the impact of sarcopenia in muscle invasive bladder cancer (MIBC) elderly patients submitted to curative radiotherapy. Patients and Methods: Patients received radiotherapy between 2013 and 2018, and the skeletal muscle index was calculated to classify them as sarcopenic or non-sarcopenic. Primary endpoints were overall survival (OS), cancer specific survival (CSS), 90-day mortality and toxicity. Results: A total of 28 patients with a median age of 85 years met our inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…After all, achieving an optimal locoregional control while limiting the onset of treatment-related adverse events, especially among frail patients ineligible for other treatments, is usually the main goal of current radiotherapy practice [19] , [20] .…”
Section: Introduction/rationalementioning
confidence: 99%
“…After all, achieving an optimal locoregional control while limiting the onset of treatment-related adverse events, especially among frail patients ineligible for other treatments, is usually the main goal of current radiotherapy practice [19] , [20] .…”
Section: Introduction/rationalementioning
confidence: 99%
“…While the first is exclusively devoted to the treatment of brain targets [12], the second is also used for treating extracranial tumors [13]. In recent years, a LINAC-based RT technique-namely Volumetric Modulated Arc Therapy (VMAT), which was typically employed for limiting radiationrelated adverse events in extracranial sites [14,15]-has been enhanced with advanced Treatment Planning Systems (TPS) to plan a simultaneous radiation dose delivery to multiple brain metastases with maximal sparing of healthy tissue, similarly to what is achievable with GK [8]. Regarding the therapeutic index, these two stereotactic techniques constantly confront dosimetric challenges, and no clinical study has yet confirmed a clear benefit of the one over the other [16].…”
mentioning
confidence: 99%
“…Conversely, neither fractionation scheme (normofractionated vs. hypofractionated radiation dose) nor therapeutic setting (radical vs. adjuvant) correlated with rectal toxicity. Additionally, the lack of any correlation between proctitis risk and age also confirms the safety of radiotherapy treatment for genitourinary cancers among elderly populations [26].…”
Section: Discussionmentioning
confidence: 84%